MAPPING ECONOMIC DEVELOPMENT TRENDS IN ISLAMIC ECONOMICS: A SYSTEMATIC LITERATURE REVIEW - Al Maulud; Umrotul Khasanah; Ismail Ismail (Ad Deenar: Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to map the development of research on economic development in Islamic economics published in reputable Scopus-indexed international journals during the period 2016–2025. Using a Systematic Literature Review (SLR) approach based on the PRISMA protocol, this study analyzes publication trends, the distribution of authors and institutions, the characteristics of topic clusters, and the direction of research innovation. The findings show that publications related to Islamic economic development have increased significantly, especially after 2020, with the largest contributions coming from Indonesia and Malaysia. Analysis using VOSviewer and Rstudio identified nine main research clusters, which include the issues of maqasid al-shariah, sustainability, sharia governance, the halal industry, green investment, zakat and community empowerment, as well as energy and the environment. In addition, the visualization of topic novelty reveals a shift in research focus from normative themes to more applied issues such as the halal supply chain, ESG, energy management, and Islamic value-based sustainable development governance models. The results of the study confirm that Islamic economics is developing as a multidisciplinary paradigm capable of responding to global challenges in the context of sustainable development. This study contributes to providing a map of knowledge and the direction of development of Islamic economic studies, although it is limited by the use of a single database and specific selection criteria. Recommendations for further research include expanding the scope of the database and combining the SLR method with in-depth qualitative analysis to identify research gaps and strengthen the theoretical construction of Islamic economic development.